Potential output growth in several industrialised countries: a comparison - Christophe Cahn; Arthur Saint-Guilhem (European Central Bank (ECB), 2007)
In this paper, we present international comparisons of potential output growth among several economies —Canada, the euro area, France, Germany, Italy, Japan, the Netherlands, the United Kingdom, and the United States— for the period 1991-2004. The main estimates rely on a structural approach where output of the whole economy is described by a Cobb-Douglas function. This framework enables us to take temporal considerations into account, depending on the assumed volatility of potential output. Moreover, this study presents two original features, in other words, the construction of consistent and homogenous capital stock series, and long-run estimates including capital-deepening effects based on a stable capital/output ratio in value terms, whereas standard estimations assume a stable ratio in volume terms. Lastly, we use univariate methods as a benchmark. Even though the final estimates are obviously sensitive to each method and the assumptions made for each of them, this paper might help to understand why some economies remained below their potential growth rate during the recent period by identifying the sources of long-run potential growth.
Keywords: C51; E32; O11; O47; 330; age of equipments; potential growth; production function; total factor productivity; Produktionspotenzial; Wirtschaftswachstum; Cobb-Douglas-Produktionsfunktion; Produktivität; Nutzungsdauer; Industrieländer